Teknik Dasar Menggunakan Videografi Di Dunia Broadcasting - Sugeng Widada; Adi Kusuma Widya Tama; Muhamad Rendi Purnama (UNIVERSITAS RAHARJA, 2019)
Along with the changing times and by utilizing the latest technological sophistication videography can be enjoyed in various ways and any variety of formats offered by technology experts in the world.There are currently 2 types of videos are available, namely analog and digital.A videographer categorized or categorize themselves into two, namely the amateur videographer and professional videographer.Amateur or professional, in fact is only the term and sheer status. Unfortunately, it seems there is a presumption of amateur videographer if the result is definitely not good.And because the feel just amateurs, someone feel legitimate only if the video footage is not good.Instead, there is a presumption that a professional videographer can certainly produce good images.